2014
DOI: 10.1007/s10753-014-9887-0
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Metabolite Compound K Alleviates Adjuvant-Induced Arthritis by Suppressing T Cell Activation

Abstract: Ginsenoside metabolite compound K (CK) is the degradation product of ginsenosides in the intestine by bacteria and has many pharmacological activities including anti-inflammatory effects. Rheumatoid arthritis (RA) is an inflammatory and autoimmune disease characterized by chronic synovial inflammation and articular damage in multiple joints. However, the effect of CK on RA remains unclear. In this study, the effect of CK on adjuvant arthritis (AA) and the underlying mechanisms that focused on T cell activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…The CD40L/CD40 signaling pathway is critically involved in the differentiation of B cells. CD40 is a 50-kDa trans-membrane glycoprotein and is expressed in B cells; its ligand, CD40L, also named We also found that CK suppressed the activation of T cells as well as production of IL-2 in AA rats (Chen et al, 2014). These results suggest that the inhibitory effect of CK on memory B cells may be T cell-dependent.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The CD40L/CD40 signaling pathway is critically involved in the differentiation of B cells. CD40 is a 50-kDa trans-membrane glycoprotein and is expressed in B cells; its ligand, CD40L, also named We also found that CK suppressed the activation of T cells as well as production of IL-2 in AA rats (Chen et al, 2014). These results suggest that the inhibitory effect of CK on memory B cells may be T cell-dependent.…”
Section: Discussionmentioning
confidence: 52%
“…Pharmacol Res 68:38-45. Wu H, Chen J, Wang Q, et al (2014). Ginsenoside metabolite compound K attenuates inflammatory responses of adjuvant-induced arthritis rats.…”
Section: Disclosure Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies showed that CK attenuated adjuvant-induced arthritis (AA) and collagen-induced arthritis (CIA) by suppressing T cell activation [10][11][12] . Our understanding of the immunopathology of autoimmune disease has been improved by recent progress in the research of T cells.…”
Section: Research Highlightmentioning
confidence: 99%